Nanoelectrode and nanoparticle based biosensors for environmental and health monitoring - Syed, Lateef Uddin (Kansas State University, 2012)
Reduction in electrode size down to nanometers dramatically enhances the detection sensitivity and temporal resolution. Here we explore nanoelectrode arrays (NEAs) and nanoparticles in building high performance biosensors. Vertically aligned carbon nanofibers (VACNFs) of diameter ~100 nm were grown on a Si substrate using plasma enhanced chemical vapor deposition. SiO[subscript]2 embedded CNF NEAs were then fabricated using techniques like chemical vapor deposition, mechanical polishing, and reactive ion etching, with CNF tips exposed at the final step. The effect of the interior structure of CNFs on electron transfer rate (ETR) was investigated by covalently attaching ferrocene molecules to the exposed end of CNFs. Anomalous differences in the ETR were observed between DC voltammetry (DCV) and AC voltammetry (ACV). The findings from this study are currently being extended to develop an electrochemical biosensor for the detection of cancerous protease (legumain). Preliminary results with standard macro glassy carbon electrodes show a significant decrease in ACV signal, which is encouraging. In another study, NEA was employed to capture and detect pathogenic bacteria using AC dielectrophoresis (DEP) and electrochemical impedance spectroscopy (EIS). A nano-DEP device was fabricated using photolithography processes to define a micro patterned exposed active region on NEA and a microfluidic channel on macro-indium tin oxide electrode. Enhanced electric field gradient at the exposed CNF tips was achieved due to the nanometer size of the electrodes, because of which each individual exposed tip can act as a potential DEP trap to capture the pathogen. Significant decrease in the absolute impedance at the NEA was also observed by EIS experiments. In a final study, we modified gold nanoparticles (GNPs) with luminol to develop chemiluminescence (CL) based blood biosensor. Modified GNPs were characterized by UV-Vis, IR spectroscopy and TEM. We have applied this CL method for the detection of highly diluted blood samples, in both intact and lysed forms, which releases Fe[superscipt]3[superscript]+ containing hemoglobin to catalyze the luminol CL. Particularly, the lysed blood sample can be detected even after 10[superscript]8 dilution (corresponding to ~0.18 cells/well). This method can be readily developed as a portable biosensing technique for rapid and ultrasensitive point-of-care applications.
Keywords: Nanobiosensor; Pathogen Detection; Nanoelectrodes; Nanoparticles; Cancerous protease detection; Electron transfer rates; Chemistry (0485)